(untitled) (Advancements in Homeopathic Research, 2022)
Gastrointestinal disorders are the one of the attention seeking conditions in day to day life which affects 10- 15% of total population. Gastrointestinal Symptom Rating Scale (GSRS) is a tool used to measure the severity and gradation of dyspepsia. Infections, gastrointestinal motor abnormalities, brain-gut interaction, visceral hypersensitivity, inflammation, central neural dysregulation, altered gut flora are main reasons for gastrointestinal disorders. Common presentations of gastro intestinal disorders are nausea, vomiting, heart burn, dyspepsia, pain abdomen, flatulency, bowel movement alteration (constipation, diarrhoea) and bleeding per rectum.Homoeopathy is asystem of medicine which is based on “Similia Similibus Curentur” and with the combination of constitutional prescription and law of similars the normal harmonious health will be maintained in all the patients.